Selenoproteins as regulators of T cell proliferation, differentiation, and metabolism. (July 2021) - Ma, Chi; Hoffmann, Peter R.
Abstract: Selenium (Se) is an essential micronutrient that plays a key role in regulating the immune system. T cells are of particular interest due to their important role in promoting adaptive immunity against pathogens and cancer as well as regulating tolerance, all of which are influenced by dietary Se levels. The biological effects of Se are mainly exerted through the actions of the proteins into which it is inserted, i.e. selenoproteins. Thus, the roles that selenoproteins play in regulating T cell biology and molecular mechanisms involved have emerged as important areas of research for understanding how selenium affects immunity. Members of this diverse family of proteins exhibit a wide variety of functions within T cells that include regulating calcium flux induced by T cell receptor (TCR) engagement, shaping the redox tone of T cells before, during, and after activation, and linking TCR-induced activation to metabolic reprogramming required for T cell proliferation and differentiation. This review summarizes recent insights into the roles that selenoproteins play in these processes and their implications in understanding how Se may influence immunity.